Romania : Financial Sector Assessment Program-Technical Note-Crisis Preparedness and Safety Net. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2018)
This Technical Note assesses the state of crisis preparedness and safety net in Romania. The bank resolution and crisis management toolkit has been significantly revamped since the last Financial Sector Assessment Program. The implementation of the Bank Resolution and Recovery Directive in Romania enhanced the National Bank of Romania's (NBR) powers to deal with failing banks, while the Bank Deposit Guarantee Fund gained greater involvement in these processes. The NBR has been charged with new responsibilities that flow from its ongoing role as supervisory and resolution authority, namely the enforcement and analysis of recovery planning requirements and the preparation of resolution plans. Some elements needed for the effectiveness to the crisis management framework are still work-in-progress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet